105k views
4 votes
Solve the equation 3(2x+2)=3x-15
x=-7
x=-17/3
x=3
x=7​

User The Budac
by
6.4k points

2 Answers

6 votes

Answer:

Explanation:

6x + 6 = 3x - 15

3x + 6 = -15

3x = -21

x = -7

Option 1 is the answer

User Treby
by
5.8k points
2 votes

3(2x+2)=3x-15

mutiply the bracket by 3

(3)(2x)(3)(2)= 6x+6

6x+6= 3x-15

move 3x to the other side

sign changes from +3x to -3x

6x-3x+6= 3x-3x-15

6x-3x+6= -15

3x+6= -15

move +6 to the other side

sign changes from +6 to -6

3x+6-6= -15-6

3x= -21

divide by 3 for both sides

3x/3= -21/3

x= -7

Answer: x= -7

User Goper Leo Zosa
by
6.3k points